1990
DOI: 10.1084/jem.172.6.1735
|View full text |Cite
|
Sign up to set email alerts
|

Interferon gamma plays a critical role in induced cell death of effector T cell: a possible third mechanism of self-tolerance.

Abstract: Engagement of the TCR can lead to a variety of consequences, such as cell proliferation, clonal anergy (1-3), and programmed cell death (4, 5). These consequences are critical for clonal selection, providing responses to nonself while preserving self-tolerance. Thus, the mechanisms that determine which of these responses will result are an essential component of self-nonself discrimination by T cells . In this report, we show that antiTCR/CD3 stimulation in the absence of costimulatoryy signals leads to cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
182
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(193 citation statements)
references
References 14 publications
(2 reference statements)
11
182
0
Order By: Relevance
“…An alternative role for glioma cells in inducing T-cell apoptosis is that glioma cells act as non-professional antigen-presenting cells which present tumour antigens to T cells but do not provide a co-stimulatory signal. Co-stimulation by professional antigen-presenting cells inhibits apoptosis in previously activated T cells (Groux et al, 1993 andLiu andJaneway, 1990). Therefore we suggest that apoptotic deletion of T cells in GBM is due to activationinduced apoptosis following antigen presentation by glioma cells and microglia.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative role for glioma cells in inducing T-cell apoptosis is that glioma cells act as non-professional antigen-presenting cells which present tumour antigens to T cells but do not provide a co-stimulatory signal. Co-stimulation by professional antigen-presenting cells inhibits apoptosis in previously activated T cells (Groux et al, 1993 andLiu andJaneway, 1990). Therefore we suggest that apoptotic deletion of T cells in GBM is due to activationinduced apoptosis following antigen presentation by glioma cells and microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis on purified CCR7 -or CCR7 + CTL showed that only the latter were capable of strongly proliferating and differentiating in full-effector cells, upon sustained antigen stimulation in vitro, accounting for the finding that only CCR7 + , but not CCR7 -cells, are capable of efficiently responding to antigen (or possibly to homeostatic cytokines) and to resist to death upon activation [5, 18, 19, [43][44][45][46]. On the other hand, under conditions of chronic infection, it is possible that memory CTL ultimately undergo exhaustion or deletion [47].…”
Section: Discussionmentioning
confidence: 99%
“…Altogether these data suggest that central memory HCV-specific CCR7 + /CD8 + T cells are potentially functional in patients with acute HCV infection, accounting for the high generation of semi-effector CCR7 -cells shown in patients in the ex vivo analyses. However, they are possibly hampered in generating efficient effector cells in vivo due to the lack of critical signals, likely provided by the sustained antigen stimulation in vitro [5,18,19,[43][44][45][46]. In accord with this hypothesis, semi-effector CCR7 -CTL were pushed to terminate the effector cell program by a brief in vitro preculture with IL-2, proposed to be a critical signal driving full-effector CTL differentiation [9,11].…”
Section: Discussionmentioning
confidence: 99%
“…Such a down-regulatory role is suggested by the observations that: (1) administration of antibody to IFN-can enhance EAE (Billiau et al, 1988;Voorthuis et al, 1990), (2) intraventricular IFN-can suppress EAE (Voorthuis et al, 1990), (3) abrogation of IFN-expression makes BALB/c mice susceptible to EAE (Krakowski and Owens, 1996), and (4) EAE is more severe in IFN-receptor deficient mice (Willenborg et al, 1996). IFN-might down-regulate EAE through its ability to induce apoptosis of activated T cells (Liu and Janeway, 1990). During the later stages of the disease, the pro-inflammatory functions of IFN-may be blocked by TGF-(Dore Duffy et al, 1996), thus allowing the protective role of IFN-to predominate.…”
Section: Discussionmentioning
confidence: 99%